THE IMPACT OF ATMOSPHERE TURBULENCE ON GUIDANCE PARAMETERS IN THE TRACKING COORDINATOR (Advances in Military Technology, 2022)
The turbulence of the atmosphere can to change the size and shape of the image target, to bring about fluctuation of the amplitude of radiation impact on modulator or photodetector, to bring about random change of position of the aim and hereby to cause random error in aiming of target and in measurement angle position of the target, possibly angular velocity, and to influence range of coordinator. The impact of the real atmosphere on output signal of optoelectronic tracking coordinator is analysed in this article.